Shari’ah advisors’ opinions on the need of shari’ah governance framework for Islamic capital market In Malaysia - Hassan, Rusni; Salman, Syed Ahmed (2017)
Board of directors play the significant role for the success of any business organization since they set the strategic objectives and vision statement which are the leading direction for the companies to follow. Because of the essential role of the board of directors, the corporate governance system has been introduced to ensure that board of directors discharge their responsibilities to the best interests of the shareholders. The failure of the giant companies such as Lehman Brothers and Enron is the example of the poor corporate governance. Conventional corporate governance system is essential in the conventional business environment and the same concept applies to the Islamic financial institutions. They need good Shari’ah governance which can mold and direct them to comply with Shari’ah in all aspects. This research proposes the best Shari’ah governance practices to mold Islamic capital market activities. Currently, there is no Shari’ah governance standards specific to Islamic capital market. This market is the backbone of the Islamic financial institutions because it is the avenue for the investment and liquidity management where the Islamic financial institutions can rely. The structured interviews were conducted to explore the core factors which should be included in preparing the best Shari’ah governance practices for Islamic capital market. Thirteen Shari’ah advisors are interviewed and it is found that the main components that should be included are related to Islamic accountability and responsibility; independency and objectivity; competency; confidentiality and commitment; consistency; Shari’ah audit and review; transparency and disclosure; corporate responsibility and ethicality. In addition to that, five more specific questions were asked for each main component and all the findings have generally the minimum mean value of 4. Thus, it is important for the future policy makers, industrial players and Shari’ah advisors to know the distinguished factors which should be the main parts of Shari’ah governance practices.